ASPIRIN HYPERSENSITIVITY IN CORONARY ARTERY DISEASE: PRACTICAL CHALLENGES AND MANAGEMENT APPROACHES - Nu Ngoc Linh, Doan; Van Tan, Nguyen (Journal of Health and Aging, 2025)
Aspirin is a cornerstone therapy for coronary artery disease (CAD), yet hypersensitivity complicates its use in clinical practice. This narrative review synthesizes contemporary evidence from studies and guidelines to provide pragmatic, evidence–based recommendations on the epidemiology, mechanisms, classification, and management of aspirin hypersensitivity. Prevalence is estimated at 0.5–1.9% in the general population and 2.6% among patients undergoing coronary angiography. In the ADAPTED (Aspirin Desensitization in Patients with Coronary Artery Disease) registry, a rapid desensitization protocol achieved a 95.4% success rate, with 80.3% of patients remaining on aspirin at 12 months. The 2025 American College of Cardiology/American Heart Association (ACC/AHA) guidelines recommend aspirin desensitization as the preferred strategy in acute coronary syndromes (ACS). In contrast, the 2024 European Society of Cardiology (ESC) guidelines recommend clopidogrel for chronic coronary syndromes (CCS) when aspirin is not tolerated. Desensitization is contraindicated in patients with a history of severe anaphylaxis. Accordingly, desensitization should be preferred whenever feasible. When it is not possible or unsuccessful, alternatives—such as cilostazol, indobufen, or P2Y12 inhibitor–based regimens with or without oral anticoagulants—may be considered based on ischemic and bleeding risk. Robust randomized controlled trials are needed to confirm the efficacy of these strategies.
Keywords: aspirin hypersensitivity; aspirin desensitization; coronary artery disease